Detrended fluctuation analysis as a complementary tool to asses Japanese quail locomotor behaviour in welfare related studies - Kembro, Jackelyn Melissa (2013)
Fil: Kembro, Jackelyn Melissa. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.